Throwing a chair could save officers’ lives during room entries - Blair, J. Pete (International journal of police science & management, 2017)
Law enforcement officers are sometimes required to perform building searches and room entries to search for, or apprehend, suspects. There have been several instances where officers have been shot while performing a room entry. To date, no research has sought to study methods to improve officer safety while performing room entries. Therefore, the purpose of this research is to assess the efficacy of utilizing everyday objects as a distraction device to slow the reaction speed of hostile suspects and give law enforcement officers a time advantage. The research utilizes a 1 × 2 experimental design with random assignment to conditions. A sample size of 113 is utilized to conduct the study. Data are presented using both a Bayesian and Frequentist style of analysis. The research suggests that law enforcement officers can slow suspect reaction times by deploying basic distraction techniques. The process of slowing suspect reaction time may save officer lives by allowing the officer to enter and assess the room while the suspect is distracted. The data utilized in this experiment and analyses can be accessed through email with the corresponding author.